Blood perfusion through ventricular assist devices induces erythrocytes to interact with leukocytes - Kylie M. Foster; Ahmed M. El Banayosy; Zheila Azartash-Namin; Phillip Coghill; James W. Long; Edgar O'Rear; Hendra Setiadi (Biochemistry and Biophysics Reports)
Implantations of Ventricular Assist Devices (VADs) have significantly improved quality of life and life expectancy of end-stage heart failure patients. However, despite the advancements in the VAD designs and patient management protocols, the VAD recipients remain at risk of attaining bleeding, infection, pump thrombosis, and stroke. Although blood trauma has been suggested as a critical factor in development of these adverse events, its consequences in inducing interactions between different types of blood cells are largely unknown.Following our recent findings on erythrocyte and leukocyte trauma in VAD recipients, we decided to explore interactions between erythrocytes and leukocytes by perfusing human whole blood through two different types of VADs, HeartMate II (HMII) and HeartMate 3 (HM3), concurrently in their respective Blood Circulatory Loop (BCL). By using a flow cytometry assay, we found increasing association between erythrocytes and leukocytes as VADs propelled blood through their BCLs. This time-dependent intercellular association was shown by increasing concomitant events of stained CD235a (specifically expressed on erythrocytes) and stained CD45 (specifically expressed on leukocytes) in the CD235a+ population. Compared to CentriMag (CM), which served as a control, VADs produced significantly higher concomitant signals. The findings described in this study have opened the need for further studies on a novel path for generation of adverse events that are commonly observed in VAD recipients, notably infection, pump thrombosis, and ischemic stroke.